2013
DOI: 10.1108/09540911311294560
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reaction of a Sn‐3.0Ag‐0.5Cu thin film during solder reflow

Abstract: Purpose -The purpose of this paper is to produce and investigate the interfacial reaction between Sn-3.0Ag-0.5Cu (SAC305) thin films and Cu substrates by solder reflow at various temperatures and times. Design/methodology/approach -SAC305 thin films were deposited on copper substrates using a thermal evaporation technique. The as-deposited SAC305/Cu was then reflowed on a hot plate at temperatures of 230, 240, 250 and 2608C for 30 s. In addition, solder reflow was conducted at a constant temperature of 2308C f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several studies for the IMC formation and growth in the reflow process have been developed. Many researchers proved that the thickness of IMC after the reflow process is controlled by reflow time and temperature [4][5][6]. Pan reported that the IMC thickness increased with higher reflow peak temperature and longer time above liquidus.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies for the IMC formation and growth in the reflow process have been developed. Many researchers proved that the thickness of IMC after the reflow process is controlled by reflow time and temperature [4][5][6]. Pan reported that the IMC thickness increased with higher reflow peak temperature and longer time above liquidus.…”
Section: Introductionmentioning
confidence: 99%